1998
DOI: 10.1161/01.hyp.32.4.693
|View full text |Cite
|
Sign up to set email alerts
|

Intralipid Enhances α 1 -Adrenergic Receptor–Mediated Pressor Sensitivity

Abstract: Abstract-The dyslipidemia in obese hypertensive persons may contribute to their increased vascular ␣-adrenergic receptor reactivity and tone. To further examine this notion, we conducted 2 studies of pressor sensitivity to phenylephrine, an ␣ 1 -adrenergic receptor agonist, in lean normotensive subjects. In the first study (nϭ6), pressor responses to phenylephrine were obtained before and during a saline and heparin infusion. On another day, pressor reactivity to phenylephrine was measured before and during in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
28
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 37 publications
4
28
0
Order By: Relevance
“…33 In conjunction with the above study, elevation of plasma NEFAs after infusion of Intralipid alone or Intralipid and heparin in lean normotensive subjects similarly reduced the dose of phenylephrine required to raise MBP by 20 mm Hg. 34 These data suggest that raising levels of plasma NEFAs and/or triglycerides enhance a 1 -adrenoceptor-mediated venoconstriction and pressor sensitivity. Other investigators reported comparably adverse effects of NEFAs on vascular function.…”
Section: Nefa and A 1 -Adrenergic Activationmentioning
confidence: 88%
“…33 In conjunction with the above study, elevation of plasma NEFAs after infusion of Intralipid alone or Intralipid and heparin in lean normotensive subjects similarly reduced the dose of phenylephrine required to raise MBP by 20 mm Hg. 34 These data suggest that raising levels of plasma NEFAs and/or triglycerides enhance a 1 -adrenoceptor-mediated venoconstriction and pressor sensitivity. Other investigators reported comparably adverse effects of NEFAs on vascular function.…”
Section: Nefa and A 1 -Adrenergic Activationmentioning
confidence: 88%
“…Nevertheless, experimental studies in humans and in animals support a relationship between NEFA and hypertension. In humans, the acute action of Intralipid/heparin infusion to raise BP suggests the involvement of NEFA in enhancing ␣ 1 -adrenoreceptormediated pressor sensitivity (25). In pigs, BP rises when plasma NEFA are elevated during an acute infusion of Intralipid/heparin (10).…”
Section: Discussionmentioning
confidence: 99%
“…NEFA levels are elevated in type 2 diabetes 9,10 and confer in nondiabetic individuals an increased risk of type 2 diabetes. 11,12 In addition, elevated NEFA levels are associated with insulin resistance [13][14][15] and hypertension, 16,17 two conditions that have been ascribed an increased risk of CVD and cerebrovascular disease. 18 -20 To address this question, we measured NEFA concentrations in diabetic and nondiabetic individuals from families with clustering of type 2 diabetes and related the findings to history of CVD in their parents.…”
mentioning
confidence: 99%